The importance of integrated skills in teaching English as a foreign language - Sh.M., Haydarov; G.H., Suyunova (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2023)
In a practical sense, one of the most crucial of these strands consists of the four primary skills of listening, reading, speaking, and writing. This strand also includes associated or related skills such as knowledge of vocabulary, spelling, pronunciation, syntax, meaning, and usage. The skill strand of the tapestry leads to optimal ESL/EFL communication when the skills are interwoven during instruction. This is known as the integrated-skill approach.